Simone Weil - Gray, Francine du Plessix 1930-2019 (A Penguin life, 2001)
Klappentext: In "Simone Weil", du Plessix Gray vividly evokes the life of a complex and intriguing figure. A patriot and a mystic, an unruly activist plagued by self-doubt, a pampered intellectual with a credo of manual labor, an ascetic who craved sensuous beauty, Simone Weil died at the age of thirty-four prematurely after a long struggle with anorexia. But her tremendous intellectual legacy foresaw many of the twentieth century's great changes and continues to influence philosophy today. Simone Weil traces this seminal thinker's transformation from privileged Parisian student to union organizer, activist, and philosopher as well as the complex evolution of her ideas on Christianity, politics, and sexuality. In this thoughtful and compelling biography, du Plessix Gray illuminates an enigmatic figure and early feminist whose passion and pathos will fascinate a wide audience of readers.